Science and Technology for the Export Product of Small and Medium Sized Enterprise (UKM) Kotaraja Rattan - Muzakir, Ully (SCAD Independent, 2019)
The objective of the Export Product Science and Technology Division (IBPE) is to boost the export growth of Small and Medium Sized Enterprises (SME) of rattan handicraft products in Aceh Besar Regency